Isolation Techniques, Structural Characteristics, and Pharmacological Effects of Phellinus Polysaccharides: A Review - Yiming Yin; Xiaolin Shi; Xiaoqing Cai; Fangrui Liu; Wenting Ni; Baohong Li; Xinhuan Wan; Meng Ren (Molecules, 2024)
Phellinus is a precious perennial medicinal fungus. Its polysaccharides are important bioactive components, and their chemical composition is complex. The polysaccharides are mainly extracted from the fruiting body and mycelium. The yield of the polysaccharides is dependent on the extraction method. They have many pharmacological activities, such as antitumor, immunomodulatory, antioxidant, hypoglycemic, anti-inflammatory, etc. They are also reported to show minor toxic and side effects. Many studies have reported the anticancer activity of Phellinus polysaccharides. This review paper provides a comprehensive examination of the current methodologies for the extraction and purification of Phellinus polysaccharides. Additionally, it delves into the structural characteristics, pharmacological activities, and mechanisms of action of these polysaccharides. The primary aim of this review is to offer a valuable resource for researchers, facilitating further studies on Phellinus polysaccharides and their potential applications.